2013
DOI: 10.1002/pmic.201300047
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and quantification of cerebral metabolic fluxes of glucose in awake mice

Abstract: Biotransformation of glucose in organs includes multiple pathways, while quantitative evaluation of percentages of its utilization for individual pathways and their spatial heterogeneity in vivo remain unknown. Imaging MS (IMS) and metabolomics combined with a focused microwave irradiation for rapidly fixing tissue metabolism allowed us to quantify and visualize metabolic fluxes of glucose-derived metabolites in the mouse brain in vivo. At 15 min after the intraperitoneal injection of (13) C6 -labeled glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 41 publications
2
73
1
Order By: Relevance
“…We investigated the distribution of lactate within E9.5 embryos using matrix-assisted laser desorption/ ionization-imaging mass spectrometry (MALDI-IMS), a useful method for visualizing the spatial distribution of individual biomolecules at a spatial resolution of ∼30 µm pitch on intact tissues (Bailey et al, 2015;Hamilton et al, 2015;Sugiura et al, 2014). Fresh frozen embryos were sectioned and analyzed by MALDI-IMS.…”
Section: Transition Of Embryonic Metabolome Profiles During Cbmentioning
confidence: 99%
“…We investigated the distribution of lactate within E9.5 embryos using matrix-assisted laser desorption/ ionization-imaging mass spectrometry (MALDI-IMS), a useful method for visualizing the spatial distribution of individual biomolecules at a spatial resolution of ∼30 µm pitch on intact tissues (Bailey et al, 2015;Hamilton et al, 2015;Sugiura et al, 2014). Fresh frozen embryos were sectioned and analyzed by MALDI-IMS.…”
Section: Transition Of Embryonic Metabolome Profiles During Cbmentioning
confidence: 99%
“…Comparison of labile metabolites distributions using di erent sampling methods. 14) e FMW-treatment successfully suppressed these changes and resulted in high quality distribution images. (FMW; focused microwave irradiation, ISF; in-situ freezing, and PEF; posteuthanized freezing method)…”
Section: )mentioning
confidence: 99%
“…Quantitatively, the ATP concentration in the PEF treated tissue was dramatically decreased by 1/10 compared to that for FMW treated tissue. 14) TISSUE THICKNESS e thickness of tissue slices can be an important factor. Comparison of labile metabolites distributions using di erent sampling methods.…”
Section: )mentioning
confidence: 99%
“…In one study, Sugiura et al, 26) we demonstrated that FMW treatment is an essential process for investigation of glucoseoriginated metabolic pathways in vivo using MS both for imaging and quanti cation.…”
Section: Fmw Is Essential For Analysis Of Glucose Metabolism In Vivo mentioning
confidence: 99%
“…In particular, we have developed several key techniques, including (i) a sample preparation procedure that eliminates the common e ect of postmortem (PM) degradation of labile metabolites, 26) and (ii) on-tissue derivatization of metabolites that could enhance the analyte ionization e ciency. 27) ese techniques have enabled visualization of diverse metabolite species, including not only abundant phospholipids [28][29][30] but also metabolites present in trace amounts such as minor amino acids, 31) nucleotides, 32,33) neurotransmitters, [34][35][36] and bioactive lipids, 37) in various tissues of diseased model animals (as summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%